Playing for Dollars : Labor Relations and the Sports Business - Staudohar, Paul D. (Book collections on Project MUSE., 1996)
Author of The Sports Industry and Collective Bargaining, an earlier version of the current volume, Staudohar describes the mechanics of contract and salary negotiations, including the pivotal issue of free agency. He explains how unions become established in sports, how the balance of power shifted between owners and players, and how the salaries of stars escalated. He investigates the gambling controversies and changing drug policies that have sometimes alienated fans and comments, as well, on the impact AIDS has had on professional sports. Sports events are media events, and Staudohar takes a look at the effects of television contracts and international expansion. He also considers the future of team sports, discussing league expansion, prospects for growth, and the issue of franchise relocation.